FAKTOR-FAKTOR YANG BERHUBUNGAN DENGAN STATUS GIZI BURUK PADA BALITA DI KOTA SEMARANG TAHUN 2017 (Studi di Rumah Pemulihan Gizi Banyumanik Kota Semarang) - Silvera Oktavia; Laksmi Widajanti; Ronny Aruben (Fakultas Kesehatan Masyarakat Universitas Diponegoro, 2017)
Severe acute malnutrition is a condition where nutritional deficiencies are seen based on nutritional status that is below the average standard determined based on the anthropometric indicator of body weight by height (WHZ)) with z-score <-3 SD and presence or absence of edema. The purpose of this study is to determine the factors associated with malnutrition status in under five child in Nutrition House of Semarang City. The type of research used is descriptive analytic quantitative research with cross sectional method. Population in this research is all mother and child who undergo recovery at Home Nutrition by sampling technique using total sampling technique that is 20. Anthropometric measurements were performed to calculate z-scores, filling out questionnaires, food recalls and food and non-family food expenditure forms. After doing the research, it is known that child suffering from severe acute malnutrition based on indicator WHZ is as many 11 people (55%). The results showed that variables associated with nutrition status were energy consumption level (p = 0,002), protein consumption (p = 0,04), and infectious disease (p = 0,000). While the variables associated with the level of energy and protein consumption is maternal nutrition knowledge and family economic status variables (p = 0.001).